Effectiveness of Using a Variety of Expository and Discussion Learning Methods in Microteaching Practice - Satrio Wibowo Budhoyono; Indah Wahyu Puji Utami (Dinasti International Journal of Education Management And Social Science, 2025)
This article aims to analyze the effectiveness of using a variety of expository and discussion methods in microteaching practice to develop the pedagogical competence of prospective history teachers.  Employing a descriptive qualitative approach, data were collected through observation, video documentation, personal reflection, and  observer feedback. The research findings reveal that the combination of expository and discussion methods fosters active students' engagement in history learning. However, time management during the microteaching learning process remains a significant challenge due its limited duration. This article encourages prospective teachers to explore diverse teaching methods to provide more meaningful learning experiences. This study is limitated  by the small sample size, relatively short research duration, and  its focus on  a single learning topic.